2011
DOI: 10.1007/s12185-011-0920-x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate dose delivery is more important than ciclosporin level in graft-versus-host disease prophylaxis following T-replete reduced-intensity sibling allogeneic stem cell transplant

Abstract: We investigated the contributions of methotrexate (MTX) and ciclosporin (CsA) prophylaxis to acute/chronic graft-versus-host disease (a/cGvHD) prevention following reduced-intensity conditioned allogeneic haematopoietic stem cell transplant (HSCT). Ninety-two fludarabine-melphalan sibling allo-SCT received CsA. Nine, 30 and 47 patients received no MTX, 2-3 doses and 4 doses, respectively. Cumulative CsA blood level to day 21 (CsA(21)) was calculated. Grades II-IV aGvHD incidence was 37.2%. In multivariate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…12 Medd et al found MTX dose omission, but not reduction, significantly increased incidence of grades 2-4 acute GVHD in reduced-intensity conditioned sibling allogeneic transplants. 29 Conversely, others have shown no difference in incidence of acute GVHD in any grade; however, used a lower dosing regimen and tacrolimus instead of CYA. 11 Our findings of poorer survival associated with MTX omission have been replicated more consistently in previous work.…”
Section: Outcomes Of Reduced Gvhd Prophylaxismentioning
confidence: 99%
“…12 Medd et al found MTX dose omission, but not reduction, significantly increased incidence of grades 2-4 acute GVHD in reduced-intensity conditioned sibling allogeneic transplants. 29 Conversely, others have shown no difference in incidence of acute GVHD in any grade; however, used a lower dosing regimen and tacrolimus instead of CYA. 11 Our findings of poorer survival associated with MTX omission have been replicated more consistently in previous work.…”
Section: Outcomes Of Reduced Gvhd Prophylaxismentioning
confidence: 99%
“…The overall effect of these omissions on subsequent acute and chronic GVHD incidence remains unclear. An earlier study showed that omission of the final day 11 MTX did not adversely affect incidence of severe acute GVHD and chronic GVHD 8) , while 2 later reports showed a greater risk for GVHD in patients who were not given all planned doses of MTX 9 , 10) . The majority of the patients in these 3 reports were adult recipients of HSCT.…”
Section: Introductionmentioning
confidence: 99%